PELAT BETON KOMPOSIT SEBAGAI LANDASAN TEMPAT BERMAIN ANAK - Sutandi, Arianti; Habib, Muhammad Saleh; Prakoso, Benedictus Brandon; Kuluq, Marcellino Awang (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2023)
Composite concrete is a material that has excellent mechanical properties. From various studies that have been carried out, it shows excellent mechanical properties, namely the compressive strength can reach 200 MPa and fracture toughness can reach above 30 MPa. The enormous compressive and flexural strength allows composite concrete to be used in various building structural elements such as beams, columns or slabs or other uses. Composite concrete is able to answer the challenges of the building construction industry to create very tall buildings and very long spans. With very large strength composite concrete can be designed with a slim so that it can reduce its own load very significantly. The research team of the Bachelor of Civil Engineering Study Program, Tarumanagara University, has developed composite concrete technology and is able to produce compressive strengths above 150 MPa and fracture toughness reaching above 30 MPa. The research team also developed the application of composite concrete in various applications such as retrofitting, bamboo joints and so on. The PkM team for the Civil Engineering Undergraduate Study Program, Tarumanagara University partnered with residents of RW 07, Banjar Wijaya Housing, Cipete Village, Pinang District, Tangerang City. Partners have problems in making children's playgrounds from thin but strong concrete. Based on the residents' difficulties in making the foundation for a children's playground that is thin but strong, the PkM team from the Department of Civil Engineering at Tarumanagara University uses composite concrete technology to make slabs as the foundation for the floor plates for children's play which is thin and strong. Beton komposit merupakan material yang mempunyai sifat mekanik sangat baik. Dari berbagai penelitian yang telah dilakukan menunjukkan sifat mekanis yang sangat baik yaitu kekuatan tekan mampu mencapai 200 MPa dan fracture toughness mampu mencapai diatas 30 MPa. Kekuatan tekan dan lentur sangat besar tersebut memungkinkan beton komposit digunakan dalam berbagai elemen struktur bangunan seperti sebagai balok, kolom ataupun pelat atau penggunaan lainnya. Beton komposit mampu menjawab tantangan industri konstruksi bangunan untuk membuat bangunan yang sangat tinggi dan bentang yang sangat Panjang. Dengan kekuatan sangat besar beton komposit dapat didesain dengan ramping sehingga mampu mengurangi bebannya sendiri dengan sangat signifikan. Tim peneliti Program Studi Sarjana Teknik Sipil Universitas Tarumanagara, telah mengembangkan teknologi beton komposit dan mampu menghasilkan kekuatan tekan di atas 150 MPa dan fracture toughness mencapai di atas 30 MPa. Tim peneliti juga mengembangkan aplikasi beton komposit pada berbagai penggunaan seperti retrofit, sambungan bambu dan sebagainya. Tim PkM Program Studi Sarjana Teknik Sipil Universitas Tarumanagara bermitra dengan warga RW 07 Perumahan Banjar Wijaya Kelurahan Cipete Kecamatan Pinang Kota Tangerang. Mitra mengalami kendala dalam membuat tempat bermain anak dari beton yang tipis namun kuat. Berdasarkan kesulitan warga untuk membuat landasan tempat bermain anak yang tipis namun kuat, tim PkM Jurusan Teknik Sipil Universitas Tarumanagara menggunakan teknologi beton komposit untuk membuat pelat pelat sebagai landasan pelat lantai tempat permainan anak yang tipis dan kuat.